DETERMINING THE GROWTH OF SHARIA COMMERCIAL BANK CURRENT ACCOUNT BALANCE AND THE NOMINAL VALUE OF THE BI-RTGS ISLAMIC BANKING TRANSACTIONS - Riski Amalia; Moh Mahrus; Dedy Mainata (Tasharruf: Journal Economics and Business of Islam, 2020)
This study aims to determine the growth of the Sharia Commercial Bank Current Account balance and the nominal value of the BI-RTGS Islamic Banking 2015-2018 transactions, how the impact of the Sharia Commercial Bank Current Account balance at Bank Indonesia on the nominal amount of BI-RTGS Islamic Banking transactions. This research uses a quantitative approach with the associative descriptive method. The population and sample in this study are all Islamic commercial banks that have registered as BI-RTGS participants. The independent variable is the Sharia Commercial Bank Current Account at Bank Indonesia for the 2015-2018 period and the dependent variable is the nominal transaction value of the BI-RTGS Islamic Banking in Indonesia for the 2015-2018 period. The data analysis techniques used are the Classical Assumption Test, Individual Significance Test (t statistical test), and Determination Coefficient Test. The results of the Individual Significant Test (t-statistical test) show that there is a significant influence between the current account balance of Islamic Commercial Banks at Bank Indonesia on the nominal amount of BI-RTGS transactions for Islamic Banking in Indonesia.